Evaluation of partial resheathing of EmboTrap III using the microcatheter (PREMIER) technique for fibrin-rich hard clots in an in vitro vessel model - Namitome, Satoshi; Nagao, Yoichiro; Shigehatake, Yuya; Matsuo, Junichi; Kawamoto, Keisuke; Kuroki, Kenji; Hayashi, Hirotaka; Nakajima, Makoto; Terasaki, Tadashi; Ueda, Mitsuharu; Shindo, Seigo (Frontiers in Neurology, 2024)
Despite the ongoing advancements in mechanical thrombectomy for large vessel occlusions causing acute ischemic stroke, successful recanalization is not achieved in all patients. One contributing factor is the presence of fibrin-rich hard clots. We proposed a new technique called the PREMIER technique, which aims to retrieve fibrin-rich clots. This study evaluated the efficacy of the PREMIER technique on fibrin-rich and erythrocyte-rich clots by comparing it with the simple use of EmboTrap III in an in vitro vessel model.The PREMIER technique involves partially resheathing a fully deployed Embotrap III (CERENOVUS, Johnson & Johnson Medical Devices, Irvine, California, USA) using a microcatheter to capture and retrieve a hard clot between the inner channel and outer cages of Embotrap III. We compared recanalization rate of the PREMIER technique with the simpleThe PREMIER technique is a novel technique for acute large-vessel occlusions caused by fibrin-rich hard clots that hinders successful recanalization during mechanical thrombectomy.